Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Nilai Perusahaan dengan Kebijakan Dividen Sebagai Variabel Intervening: Studi Kasus Perusahaan Manufaktur Makanan dan Minuman yang Terdaftar di BEI Tahun 2020-2023 - Ardian Rossi Hendriyanto; Triyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the Effect of Profitability, Liquidity, and Leverage on Company Value with Dividend Policy as an Intervening Variable. The method used in this study is a quantitative method. The population in this study is Food and Beverage Manufacturing Companies Listed on the IDX in 2020-2023. The sampling used in this study was a purposive sampling technique with a total of 68 companies. In this study, the data analysis technique used was SPSS software. The results of the study show that Profitability and Liquidity have a positive effect on Dividend Policy, while Leverage does not show a significant effect. Profitability also increases Company Value, while Liquidity and Leverage have no effect. Dividend Policy also has a positive impact on Company Value. However, Dividend Policy is unable to mediate